PENGARUH PENGGUNAAN ALAT PERAGA DAN VIDEO PEMBELAJARAN TERHADAP PEMAHAMAN MATERI DIKLAT JURU LEDAK KELAS II TAHUN 2021 - Yudiana Hadiyat; Leni Nurliana (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2021)
The success of blasting activities can be seen from three aspects, namely the absence of accidents, achieving production targets and the absence of impact on the environment. The success of the blasting is influenced by the knowledge, skills and work attitude (competence) of the Blaster. One alternative to increase competence can be done through effective education and training. This study aims to determine the extent of the effectiveness of teaching aids and learning videos in increasing the understanding of training participants on the material presented. This research use a questionnare that is submitted to the participants of Class II Explosive Training Class IV 2021 at PPSDM Geominerba. The results of the questionnaire were processed using statistical methods through several analyzes, namely regression analysis and analysis of variance. From the results of data processing, it is found that there are three variables that have an influence on increasing the understanding of class II Explosive Training participants, namely the use of teaching aids and learning videos can increase the focus of training participants (X1), increase enthusiasm (X2) and reduce the boredom of training participants during training take place (X3). Variable X3 has the greatest influence among the other two variables on increasing participants' understanding. Based on the results of the analysis of variance, it can be seen that teaching aids and learning videos are proven to increase the effectiveness of Class II Explosive Training.